Murine neural crest stem cells and embryonic stem cell‐derived neuron precursors survive and differentiate after transplantation in a model of dorsal root avulsion. (21st April 2014) - Konig, Niclas; Trolle, Carl; Kapuralin, Katarina; Adameyko, Igor; Mitrecic, Dinko; Aldskogius, Hakan; Shortland, Peter J.; Kozlova, Elena N.
Abstract: Spinal root avulsion results in paralysis and sensory loss, and is commonly associated with chronic pain. In addition to the failure of avulsed dorsal root axons to regenerate into the spinal cord, avulsion injury leads to extensive neuroinflammation and degeneration of second‐order neurons in the dorsal horn. The ultimate objective in the treatment of this condition is to counteract degeneration of spinal cord neurons and to achieve functionally useful regeneration/reconnection of sensory neurons with spinal cord neurons. Here we compare survival and migration of murine boundary cap neural crest stem cells (bNCSCs) and embryonic stem cells (ESCs)‐derived, predifferentiated neuron precursors after their implantation acutely at the junction between avulsed dorsal roots L3–L6 and the spinal cord. Both types of cells survived transplantation, but showed distinctly different modes of migration. Thus, bNCSCs migrated into the spinal cord, expressed glial markers and formed elongated tubes in the peripheral nervous system (PNS) compartment of the avulsed dorsal root transitional zone (DRTZ) area. In contrast, the ESC transplants remained at the site of implantation and differentiated to motor neurons and interneurons. These data show that both stem cell types successfully survived implantation to the acutely injured spinal cord and maintained their differentiation and migration potential. These data suggest that, depending on the source of neural stem cells, they can play different beneficial roles for recovery after dorsal root avulsion. Copyright © 2014 John Wiley & Sons, Ltd.